2013
DOI: 10.5664/jcsm.3264
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a Combination of Validated Questionnaires and Level III Portable Monitor with Polysomnography to Diagnose and Exclude Sleep Apnea

Abstract: Study Objectives: Questionnaires have been validated as screening tools in adult populations at risk for obstructive sleep apnea (OSA). Portable monitors (PM) have gained acceptance for confi rmation of OSA in some patients with a high pretest probability of the disorder. We evaluated the combined diagnostic utility of 3 validated questionnaires and a Level III PM in the diagnosis and exclusion of OSA, as compared with in-laboratory polysomnography (PSG) derived apnea hypopnea index (AHI). Methods: Consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 28 publications
2
42
0
1
Order By: Relevance
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…62 We identified ten studies, involving primarily middle-aged, obese males suspected of OSA that evaluated the performance of STOP-BANG questionnaire against PSG in the identification patients with OSA. 42,[49][50][51][52][63][64][65][66][67] The overall findings reveal that the STOP-BANG questionnaire had high sensitivity, but low specificity for the detection of OSA. These findings became more pronounced when higher levels of OSA category cutoffs were considered.…”
Section: Stop-bang Questionnairementioning
confidence: 99%
“…Several studies have shown that portable diagnosis and management of OSAHS in sleep centres may produce comparable patient outcomes with in laboratory sleep studies (15)(16)(17) and that the predictive values of oximetry in high risk populations as ours are high (18,19). The degree of oxygen desaturation varies between individuals depending on baseline arterial oxygen saturation, the presence or absence of lung disease and lung volumes (20)(21)(22)(23) COPD or heart failure. Unfortunately we did not perform pulmonary function testing for all our patients.…”
Section: Discussionmentioning
confidence: 89%
“…In the study of Pereira et al (22) previously well-validated questionnaires were evaluated to diagnose or exclude OSAHS in combination with a level III portable monitor. They found that objective data from the portable monitor was superior to questionnaires in OSAHS diagnosis and that the use of questionnaires did not further enhance the diagnostic utility of the portable device.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires have to be supplemented by the use of a level III study [33] or postoperative respiratory monitoring [4] to identify OSA. The use of a level III study in patients being at risk for OSA is needed for reliably ruling out OSA preoperatively and can establish a definite intraand postoperative plan.…”
Section: Osa and Postoperative Complicationsmentioning
confidence: 99%